User Satisfaction and Net Benefits in Lecturer Secretariat Monitoring Systems: Kepuasan Pengguna dan Manfaat Bersih Sistem Monitoring Sekretariat Dosen - Azahra, Athaya Putri; Basyah, Baby Lolita (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Digital attendance systems support efficient and accurate higher education administration. Specific Background: The Lecturer Secretariat Monitoring Website is used for online lecturer attendance input and monitoring. Knowledge Gap: Prior attendance system studies mainly discuss development and functionality, while empirical evaluation of information quality, system quality, service quality, usage, satisfaction, and net benefits remains limited. Aims: This study analyzes user satisfaction and net benefits using the DeLone and McLean model. Results: Data from 80 administrator users were analyzed using PLS-SEM with SmartPLS. All indicators were valid and reliable. Information quality, system quality, and service quality were significantly related to usage and user satisfaction, while usage and user satisfaction were significantly related to net benefits. The model showed adequate predictive ability, with R-square values of 0.440 for usage, 0.464 for user satisfaction, and 0.522 for net benefits. Novelty: This study provides an empirical evaluation of a lecturer secretariat monitoring website and confirms the role of usage in explaining satisfaction. Implications: The findings support improvements in service quality, user experience, access, and academic system integration. Highlights• All indicators were valid and reliable in the PLS-SEM assessment.• Usage and satisfaction showed significant relationships with perceived benefits.• The model demonstrated adequate predictive ability. KeywordsUser Satisfaction; Net Benefits; DeLone And McLean; PLS-SEM; Website Monitoring